Introduced Spiders in Panama: Species Distributions and New Records - Daniel Murcia-Moreno; Dumas Gálvez (Biology, 2024)
Biological invasions occur when organisms are moved from their native range and introduced into new areas, where they can spread and become a potential risk for native organisms. Invasive species are well recorded for vertebrates, plants and a number of invertebrates. A taxa for which there is a lack of information in some countries are arachnids, and this is the case of reports on introduced species in Panama. Here, we report the first list of introduced spider species in the country as a result of reviewing scientific literature, online databases, museum collections and carrying out field collections. We report six new introduced species out of a total of 31 species, belonging to 10 families and 25 genera. A large proportion of these species originated from Asia. Moreover, most of the species, with historic data available, have expanded their distribution in the country. We also present a list of species that might be already present in the country or may be introduced in the future. Our work highlights the capability of spiders to invade and spread into new territories. Therefore, monitoring policies and control strategies should also consider them as potential risk for local ecosystems.